DC women of action - Fontana, Shea (Chronicle Books, 2019)
Presents illustrated profiles of some of the most powerful, fiercest, and independent female Super Heroes and Super Villains in the DC Universe, from Wonder Woman and Lois Lane to Catwoman, Amanda Waller, and Harley Quinn. Includes quotations from some of the artists and writers who have worked over the years to bring these characters to life in the comics.